Das neue Delta des Rio Sinú an der karibischen Küste Kolumbiens.: Geographische Interpretation und kartographische Auswertung von Luftbildern - Troll, Carl; Schmidt-Kraepelin, Ernst; Guhl, Ernesto (ERDKUNDE, 1965)
In 1942-43 an important change took place in the outlet region of the Rio Sinú which affected the geographical situation, the topography and hydrography and in consequence also the economy. Until then, after approaching the open sea near Tinajones in a meandering course to within a few hundred yards, the river turned eastwards behind the beach ridge and, forming a delta, discharged into the Bahia de Cispata. Natural indentations of the silt righ delta distributaries facilitated extensive rice cultivation by peasants. The Cispata distributary was suitable for steam ship navigation from Cartagena de las Indias to Lorica and Montena on the middle Sinú. In 1942-43 the Sinú breached the beach ridge at Tina jones and the Boca de Tinajones was formed; since then the river has been building up a new delta on this straight coastline while simultaneously the supply of fresh water to the distributaries of the abandoned delta was so much reduced that saltwater penetrated upstream and ruined the rice fields. In addition the Cispata distributary ceased to be navigable and navigation in the new delta is quite impossible owing to sand bars. The situation prior to the catastrophe is known through a journey made by C. Troll in 1929 and through air photo graphs of SCADTA taken in the 1920s and in 1938. Information for the time after the breach is based on air photo graphs of the years 1945, 1948 and 1957, and further on oral reports and some documents, both of which the authors are grateful to have received through Herr E. Guhl (Bogota). The result of the evaluation of this material is that the breach was aided by human interference with the natural drainage conditions. Already at Tinajones the Sinú used to be an elevated river confined within levees (bancos). As early as 1929 small parallel canals which had been dug for irrigation of pastures and drainage after floods existed at the critical spot. They helped the Sinú to leave its bed. Furthermore at the double meander at Tinajones the river was shortened by cutting a canal across in the hope thus to increase the water supply to the rice growing area and to improve navigation. However, the increased current below the cutting resulted in a congestion of water in the river bed which in turn led to the lateral breach of the Sinú directly to the open sea. Today this change of course is irreversible. The cartographic evaluation of the air photographs carried out by E. Schmidt-Kraepelin made it possible to ascertain the change of the river bed and growth of the new delta in greater detail. In 1957, ile. 14-15 years after the new delta began to be built up it had an area of 693 ha (1,712 acres). In the years 1945-57 its daily increase rate was 1,565 sq. m. (16,845 sq. ft.).